Sinopse de Myrtaceae e Flora de Salicaceae do Parque Nacional do Iguaçu - Conceição , Lazaro Henrique Soares de Moraes (2021)
The Iguaçu National Park (ParNa Iguaçu) is a conservation unit that comprises the largest remnant of Seasonal Semideciduous Forest in the country, also comprising a small region of Mixed Ombrophilous Forest. The objective of the present research was to carry out the taxonomic treatment of Myrtaceae and Salicaceae from the Iguaçu National Park. 17 field expeditions were carried out between May May 2019 and March 2020 in two areas composed of Seasonal Semideciduous Forest and a transition area of this formation with Mixed Ombrophilous Forest. The collected samples were deposited in the UNOP herbarium and the specimens present in the EVB, HCF and UNOP herbaria, as well as in the Reflora and speciesLink virtual herbaria were analyzed. Through these surveys, 26 species of Myrtaceae and eight species of Salicaceae were registered, distributed in seven and four genera, respectively. Eugenia myrcianthes, Myrceugenia euosma, Myrcia glomerata, Myrcia palustris, Myrcia oblongata, Psidium guineense, Psidium striatulum and Xylosma venosa are new records for the park, as well Banara parviflora, Psidium striatulum, Xylosma ciliatifolia and Xylosma venosa are new records in Seasonal Semideciduos Forest